Post-SARS-CoV-2 infection and post-vaccine-related neurological complications share clinical features and the same positivity to anti-ACE2 antibodies - Bellucci, Margherita; Bozzano, Federica Maria; Castellano, Chiara; Pesce, Giampaola; Beronio, Alessandro; Farshchi, Alireza Hajabbas; Limongelli, Alessandro; Uccelli, Antonio; Benedetti, Luana; De Maria, Andrea (Frontiers in Immunology, 2024)
Introduction. A potential overlap in symptoms between post-acute COVID-19 syndrome and post-COVID-19 vaccination syndrome has been noted. We report a paired description of patients presenting with similar manifestations involving the central-(CNS) or peripheral nervous system (PNS), following SARS-CoV-2 infection or vaccination, suggesting that both may have triggered similar immune-mediated neurological disorders in the presence of anti-idiotype antibodies directed against the ACE2 protein.Patients and methods. Four patients exhibited overlapping neurological manifestations following SARS-CoV-2 infection or vaccination: radiculitis, Guillain-Barré syndrome, and MRI-negative myelitis, respectively, sharing positivity for anti-ACE2 antibodies. Autoantibodies against AQP-4, MOG, GlyR, GAD, amphiphysin, and onconeural antibodies for CNS syndromes, and antiganglioside antibodies for PNS syndromes tested negative in all patients. Discussion. Anti-idiotype antibodies against ACE2 have been detected in patients recovered from COVID-19 infection, and it has been hypothesized that such antibodies may mediate adverse events following SARS-CoV-2 infection or vaccination, resulting in activation of the immune system against cells expressing ACE2, such as neurons. Our data reveal clinically overlapping syndromes triggered by SARS-CoV-2 infection or vaccination, sharing positivity for anti-ACE2 antibodies. Their presence, in the absence of other classic autoimmune markers of CNS or PNS involvement, suggests that they might play an active role in the context of an aberrant immune response. Conclusion. Anti-idiotype antibodies directed against ACE2 may be triggered by both SARS-CoV-2 infection and vaccination, possibly contributing to neurological autoimmune manifestations. Their pathogenic role, however, remains to be demonstrated in large-scale, more structured studies.